(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Streptococcus pneumoniae is the main cause of community-acquired pneumonia worldwide; pneumonia occurs sporadically in most cases, but rare outbreaks have been reported. We describe an outbreak occurred in a 21-guests nursing home for elders in Aosta (Italy); outbreak occurred in april 2014 over a 2 weeks period, resulting in 12 out 20 guests affected (all with high fever and respiratory symptoms), two deaths (at home), nine patients referred to Hospital Emergency Room, and eight admissions. Urinary streptococcus antigen was positive in seven out of eight patient tested. None of the nursing home guests were vaccinated against Streptococcus pneumoniae The Hospital Medical Direction and Public Health Service gave support and adopted strategies to contain the outbreak spread. We underline the need for pneumococcal vaccination in nursing homes/ Long-term care facilities; accurate check of hygiene behaviours in those setting is also mandatory.